Computational methods in systems biology : 15th International Conference, CMSB 2017, Darmstadt, Germany, September 27-29, 2017, Proceedings /: 15th International Conference, CMSB 2017, Darmstadt, Germany, September 27-29, 2017, Proceedings. (2017) - Unknown
No abstract available